PELATIHAN DAN PENYULUHAN PEMANFAATAN BUAH PEPAYA SEBAGAI MPASI UNTUK MENCEGAH STUNTING - Ma’rifatun Izati; Liberta Isnanida Alkausari; Fenti Aprilia Lailatulsifa; Indra Tama Saputra; Insania Cantika Sari; Intan Agustiana; Lhuzziana Rizky Afriliantiko; Felicia Regina Oktavianti; Lutfhi Berlian Shandra; Mada Cahya Rizki Artianti; Muhammad Anang Maulana; Lilies Wahyu Ariani; Ririn Suharsanti (Jurnal Pengabdian IKIFA, 2025)
Stunting is a chronic nutritional problem that has a negative impact on children's growth and development. Preventing stunting requires optimal nutritional intervention, one of which is through the provision of nutritious complementary foods (MPASI). Papaya fruit (Carica papaya) is known to be rich in vitamin A, vitamin C, fiber, and antioxidants that are beneficial for children's health. This community service activity aims to provide counseling for PKK mothers about the benefits of papaya as a component of MPASI in efforts to prevent stunting in children aged 6-24 months. Community service activities took place on May 19 2024 in the PKK group RT 01 RW 03, Jatisari Village, Mijen District, Semarang City, Central Java. The activity was attended by 30 mothers who accompanied their children to start MPASI. The community service methods used include literature reviews for analysis of the nutritional content of papaya fruit, making MPASI from papaya fruit, counseling about the benefits and how to make MPASI from papaya fruit in the form of pudding and jam, and a trial of providing papaya-based MPASI to the target group. Evaluation in the form of taste responses includes texture, aroma, taste, and appearance. With counseling about the benefits and how to make papaya-based MPASI, the community can make variations of MPASI that are more attractive to children.